2022
DOI: 10.3390/biology11020266
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Whole-Body Vibration Combined with Multicomponent Training on the Risk of Falls and Quality of Life in Elderly Women with Osteoporosis: Study Protocol for a Randomized Controlled Clinical Trial

Abstract: Osteoporosis and the risk of falls increase the risk of fractures and events of falls. Prescriptions and programs for different forms of exercise have different impacts on the risk of falls, and exercises from multiple categories of whole-body vibration can be effective. This study aims to evaluate the effectiveness of whole-body vibration (WBV) protocol combined with multicomponent training (MCT) in elderly women with osteoporosis and their history of falls. Our proposal is a protocol for a randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…A study by Braz et al . 37 in 2022 similarly demonstrated that older women who had experienced falls had a higher prevalence of osteoporosis due to reduced physical activity, ultimately negatively impacting their quality of life. In 2019, Labens et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Braz et al . 37 in 2022 similarly demonstrated that older women who had experienced falls had a higher prevalence of osteoporosis due to reduced physical activity, ultimately negatively impacting their quality of life. In 2019, Labens et al .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of different frequencies of WBV have been studied in some diseases, such as: Osteoarthritis [5]; Osteoporosis [6,7]; Diabetes [8,9]; Sedentary elderly women [10]; Metabolic syndrome [11]; Patellofemoral pain [12]; Overweight and obesity [13]; Systemic lupus erythematosus [14]; Multiple sclerosis [15]; Down syndrome [16]; Parkinson's disease [17,18]. Despite the broad applicability of WBV to individual health, there are differences in WBV protocols in terms of defining amplitude, frequency, and duration to achieve rapid recovery.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…From the contributing studies in this category, we can mention Martins et al [ 3 ], Cuenca-Zaldivar et al [ 4 ]. Dos Santos et al [ 5 ], Maciejczyk et al [ 6 ], Dufournet et al [ 7 ], Shabat et al [ 8 ], An et al [ 9 ], Martínez-Jiménez et al [ 10 ], Wang et al [ 11 ], Ofran et al [ 12 ], Wang et al [ 13 ], Rostron et al [ 14 ], Silva Caiado et al [ 15 ], Arenales Arauz et al [ 16 ], Souto Braz et al [ 17 ], and Van Heuvelen et al [ 18 ] with an Reporting Guidelines for Whole-Body Vibration Studies in Humans, Animals and Cell Cultures. In the third category, the optimization of athlete performance was discussed in the papers of Brambilla et al [ 19 ], Strutzenberger et al [ 20 ], and Kiers et al [ 21 ].…”
Section: Introductionmentioning
confidence: 99%